Robotic Assisted Surgery in Pediatric Urology: Current Status and Future Directions - Chen, Catherine J.; Peters, Craig A. (Frontiers in Pediatrics, 2019)
The evolution of robotic surgical technology and its application in Pediatric Urology have been rapid and essentially successful. Further development remains limited in three key areas: Procedural inefficiencies, cost and integration of surgical and clinical information. By addressing these challenges through technology and novel surgical paradigms, the real potential of surgical robotics in pediatric, as well as adult applications, may ultimately be realized. With this evolution, a continued focus on patient-centered outcomes will be essential to provide optimal guidance to technical innovations.